Optimizing response to gefitinib in the treatment of non-small-cell lung cancer - Pietro Carotenuto; Cristin Roma; Anna Maria Rachiglio; et al (Dove Medical Press, 2011)
Pietro Carotenuto1, Cristin Roma1, Anna Maria Rachiglio1, Raffaella Pasquale1, Renato Franco2, Giuseppe Antinolfi3, Francovito Piantedosi4, Alfonso Illiano5, Gerardo Botti2, Alessandro Morabito6, Nicola Normanno7, Antonella De Luca71Pharmacogenomic Laboratory, CROM – Centro Ricerche Oncologiche di Mercogliano, Avellino, Italy; 2Surgical Pathology Unit, INT Fondazione "G. Pascale", Naples, Italy; 3Surgical Pathology Unit, Monaldi Hospital, Naples, Italy; 4Pneumoncology DH Unit, Monaldi Hospital, Naples, Italy; 5Pneumoncology Unit, Monaldi Hospital, Naples, Italy; 6Medical Oncology, Thoracic Department, INT Fondazione "G. Pascale", Naples, Italy; 7Cell Biology and Biotherapy Unit, INT Fondazione "G. Pascale", Naples, ItalyAbstract: The epidermal growth factor receptor (EGFR) is expressed in the majority of non-small-cell lung cancer (NSCLC). However, only a restricted subgroup of NSCLC patients respond to treatment with the EGFR tyrosine kinase inhibitor (EGFR TKI) gefitinib. Clinical trials have demonstrated that patients carrying activating mutations of the EGFR significantly benefit from treatment with gefitinib. In particular, mutations of the EGFR TK domain have been shown to increase the sensitivity of the EGFR to exogenous growth factors and, at the same time, to EGFR TKIs such as gefitinib. EGFR mutations are more frequent in patients with particular clinical and pathological features such as female sex, nonsmoker status, adenocarcinoma histology, and East Asian ethnicity. A close correlation was found between EGFR mutations and response to gefitinib in NSCLC patients. More importantly, randomized Phase III studies have shown the superiority of gefitinib compared with chemotherapy in EGFR mutant patients in the first-line setting. In addition, gefitinib showed a good toxicity profile with an incidence of adverse events that was significantly lower compared with chemotherapy. Therefore, gefitinib is a major breakthrough for the management of EGFR mutant NSCLC patients and represents the first step toward personalized treatment of NSCLC.Keywords: gefitinib, EGFR, NSCLC, EGFR mutations